Pembinaan Bahasa Indonesia: Bagaimana Strateginya di Era Digital - De San San Nurhayati; Jelita Maulida Nurhamidah; Pemmy Meisya; Yuni Ertinawati (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research is motivated by the widespread use of non-standard Indonesian on social media, which has resulted in low public awareness of the importance of implementing Indonesian according to the rules.The purpose of this study is to analyze Instagram users’ awareness of using standard Indonesian words and to assess the effectiveness of language coaching through social media. The research employed a qualitative descriptive method with a case study approach, where data were collected through polls using the Instagram Story feature, observation of uploaded content, and analysis of audience interactions between account managers and followers. The findings show that most social media users still tend to use nonstandard word forms in daily communication. However, after receiving coaching through educational content, there was a significant improvement in understanding and applying standard word forms. This study concludes that Instagram can serve as an effective and engaging medium for language development, as it can reach diverse audiences and encourage users to be more aware, responsible, and wise in using proper Indonesian according to the norms of the Kamus Besar Bahasa Indonesia (KBBI) and the Pedoman Umum Ejaan Bahasa Indonesia (PUEBI).